Porous niobium interlayer assisted brazing method

By using a porous niobium intermediate layer in a brazing system of composite materials or ceramics and metals, the problem of high residual stress in the brazed joint is solved, and the mechanical properties and reliability of the joint are significantly improved.

CN119747783AInactive Publication Date: 2025-04-04JIANGSU UNIV

Patent Information

Application Number
CN202510061902.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Composite materials or ceramics and metals have high residual stresses in the brazed joints, resulting in insufficient structural stability and mechanical properties.

Method used

The brazing method of porous niobium intermediate layer assists composite material or ceramic and metal is adopted. By adding porous niobium intermediate layer to the brazing system, the interface structure is improved, the thermal expansion coefficient of the weld is reduced, and the plastic toughness of the brazing seam is improved.

Benefits of technology

It significantly reduces the high residual stress of the joint after welding, improves the comprehensive mechanical properties of composite materials or ceramics and metal joints, and enhances the reliability and durability of the joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747783A_ABST
    Figure CN119747783A_ABST
Patent Text Reader

Abstract

The invention discloses a porous niobium interlayer assisted brazing method, and relates to a method for improving the brazing performance of a composite material or ceramic and metal. The method aims at solving the problems that a traditional porous middle layer is poor in performance, high residual stress of a composite material or ceramic and metal brazed joint is difficult to relieve, the toughness of the joint is poor, and the strengthening effect on the brazed joint is limited. The method mainly comprises the following steps: 1, pretreating a base material, a brazing filler metal and a porous niobium intermediate layer; and secondly, the base metal, the brazing filler metal and the porous niobium middle layer are assembled and placed in a vacuum furnace to be brazed, and a to-be-welded piece is obtained. The interface structure can be effectively improved, the plasticity, toughness and high-temperature mechanical property of a brazing seam are improved, the thermal expansion coefficient of the brazing seam is reduced, residual stress is released, the mechanical property of a composite material or ceramic and metal brazing joint is remarkably improved, and the high-temperature strength of the joint is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of porous material preparation and welding, and relates to a method for brazing a porous niobium intermediate layer-assisted composite material or ceramic with a metal. Background Art

[0002] In the manufacture of aerospace engine thrust chambers, it is crucial to connect the composite nozzle and the metal combustion chamber. Traditional bolt connections are difficult to meet the needs due to their heavy weight, poor strength adaptability, and easy failure of graphite sealing rings. The difficulty in connecting composite materials or ceramics to metals lies in the mismatch of thermal expansion coefficients. Thermal cycles will produce high residual stresses, affecting structural stability. In the past, the method of introducing high-plasticity metal foil or low thermal expansion coefficient ceramic reinforcement phase into the brazing seam could improve the gradient transition of the brazing seam properties to a certain extent, but the effect was not good due to the problem of stress concentration caused by the segregation of the second phase. Although there is improvement in the use of a porous material intermediate layer with a three-dimensional network structure, the commonly used foam copper, nickel and porous ceramic materials have the problems of high thermal expansion coefficient, poor high temperature performance or poor wettability, and high brittleness, which limits their application.

[0003] Compared with the above-mentioned traditional porous metal (copper, nickel) materials, metallic niobium not only has a suitable thermal expansion coefficient, which can reduce the residual stress of the joint, but also has excellent high-temperature mechanical properties and can cope with extreme working conditions. In addition, niobium has excellent chemical stability and can maintain structural stability, which helps to exert its unique strain tolerance of the network skeleton. Compared with porous ceramics, porous niobium has better brazing wettability, plasticity and toughness, is not prone to brittle fracture when subjected to stress, and can effectively buffer the stress concentration of the connection part under complex working conditions to ensure the reliability of the connection. Porous ceramics are often brittle and prone to crack propagation under thermal cycles or mechanical stress, resulting in connection failure. In addition, the thermal conductivity of porous niobium is relatively high, and the heat transfer during brazing is more uniform, which is conducive to forming a good metallurgical bond and improving the quality of the joint. In contrast, the thermal conductivity of porous ceramics is lower, which may lead to problems such as local overheating or incomplete penetration during brazing.

[0004] Therefore, the use of porous niobium as an intermediate layer to assist in the heterogeneous brazing connection of composite materials or ceramics and metals is of great significance to the development of the aerospace field and is an urgent need to achieve high-quality and high-reliability heterogeneous connections. Summary of the invention

[0005] The present invention aims to solve the problem of large residual stress in brazed joints of composite materials or ceramics and metals, and proposes a method for brazing composite materials or ceramics and metals with a porous niobium intermediate layer. The porous niobium intermediate layer used in this patent can effectively improve the interface structure, increase the plastic toughness of the brazing seam and reduce the thermal expansion coefficient of the brazing seam, thereby alleviating the high residual stress of the joint after welding and significantly improving the comprehensive mechanical properties of the composite material or ceramic and metal joints.

[0006] The specific steps of the basic technical solution of the present invention are summarized as follows: Step 1: Ultrasonic clean the composite material or ceramic to be welded in ethanol for 5 to 15 minutes and dry it in an oven; Step 2: The clean composite material or ceramic surface to be welded obtained in step 1 is polished with 600-2000 mesh silicon carbide sandpaper to remove scratches on the composite material or ceramic surface to be welded, and then ultrasonically cleaned in ethanol for 5-15 minutes, and placed in an oven at 60-80°C for drying and set aside; the metal is polished with 400 mesh, 600 mesh and 800 mesh sandpaper in turn, and then ultrasonically pretreated with ethanol for 5-15 minutes, and placed in an oven at 60-80°C for drying and set aside.

[0007] Step 3: placing a commercially available active brazing material between the textured composite material or ceramic obtained in step 2 and the metal surface to be welded to complete the brazing assembly; Step 5: Place the welded assembly from step 4 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3 × 10 –3 Pa, then 5 ~ 30 ℃ min –1 The vacuum brazing furnace is heated to 30-120°C above the melting point of the brazing material at a heating rate, then kept warm for 5-60 min, and finally heated at 1-10°C min –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain a composite material or ceramic and metal brazing joint.

[0008] Compared with the patent "A method for improving the brazing performance of TC4 and ceramics by adding a foam copper intermediate layer" (application number: CN106270889A), the present invention has the following technical advantages: (1) The melting point of foamed Cu is only 1084°C, which is very easy to soften and fail quickly in the high-temperature thermal shock service environment of the aerospace engine nozzle, while the melting point of porous niobium is higher, which can ensure the high-temperature strength of the joint; (2) The thermal expansion coefficient of porous niobium is relatively lower, which can reduce the thermal expansion coefficient of the weld and relieve residual stress, while the thermal expansion coefficient of foamed Cu is larger and much higher than the thermal expansion coefficient of composite materials or ceramics, which restricts its effect of relieving high residual stress in the joint.

[0009] Compared with the patent "A method for auxiliary brazing of porous negative expansion ceramic intermediate layer" (authorization announcement number: CN109369209B), the present invention has the following technical advantages: (1) Porous niobium has good metallurgical compatibility with the brazing alloy. In contrast, the brazing alloy has poor wettability on ceramics, which may lead to defects in the joint or increase the cost and complexity of process optimization; (2) Porous niobium has better machinability than ceramics and is simple to prepare, while porous ceramics are difficult to process and prone to slagging; (3) Porous niobium has higher plasticity and toughness than ceramics, which helps to improve the toughness of the joint, but too high a ceramic content will increase the brittleness of the joint. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a SEM photo of the interface of the brazed joint between C / C composite material and GH3536 alloy using a porous niobium intermediate layer and BNi2 (6.0-8.0 Cr, 4.0-5.0 Si, 2.75-3.5 B, 2.5-3.5 Fe, bal. Ni, wt%) active brazing foil. It can be clearly observed from the figure that the interface structure of the brazed joint is complete, and there are no defects such as cracks and holes. The joint interface can be divided into three reaction zones, from left to right, which are the reaction layer area close to the C / C composite side, the middle area of ​​the weld, and the area close to the GH3536 alloy side. In the reaction layer area on the C / C composite side, dark gray strip-shaped chromium carbide is generated, and at the same time, gray-white niobium carbide reactants are dispersed in this area. The formation of niobium carbide helps to fill the pores and significantly enhances the bonding strength of the interface. In the brazing seam area, the boron element diffuses evenly and reacts with elements such as Cr in the brazing seam area to form complex borides. In the GH3536 alloy side area, continuous reactants are generated. These reactants are mainly complex compounds formed by the reaction of elements in the alloy with elements in the brazing material and other diffused elements at high temperatures.

[0011] Figure 2 The shear strength of C / C-GH3536 joints brazed without an intermediate layer and with a porous niobium intermediate layer was studied. The results showed that compared with the direct brazed joints, the room temperature shear strength of the C / C-GH3536 joints brazed with a porous niobium intermediate layer increased by 50% to 44.1 MPa. DETAILED DESCRIPTION

[0012] The present invention describes a method for assisting brazing with a porous niobium intermediate layer, which solves the problem of excessive residual stress in the joint due to large difference in thermal expansion coefficients during brazing of composite materials or ceramics and metals, and poor mechanical properties of the joint due to poor dispersion and easy loss of active elements when traditional reinforcement phases are added to the brazing seam, by adding a porous niobium intermediate layer to the brazing system of composite materials or ceramics and metals. The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any combination of the specific embodiments.

[0013] Specific implementation method 1: The method for auxiliary brazing of a porous niobium composite intermediate layer described in this implementation method is mainly divided into the following steps: Step 1: ultrasonically clean the C / C composite material to be welded in ethanol for 5 to 15 min, and then dry it in an oven; Step 2: The clean composite material or ceramic surface to be welded obtained in step 1 is polished with 600, 800, 1000, 1200, 1500, and 2000 mesh silicon carbide sandpaper to remove scratches on the composite material or ceramic surface to be welded, and then ultrasonically cleaned in ethanol for 5 to 15 minutes, and placed in an oven at 60 to 80°C for drying and standby; the metal is polished with 400 mesh, 600 mesh, and 800 mesh sandpaper in turn, and then ultrasonically pretreated with ethanol for 5 to 15 minutes, and placed in an oven at 60 to 80°C for drying and standby.

[0014] Step 3: placing a commercially available active brazing material between the textured composite material or ceramic obtained in step 2 and the metal surface to be welded to complete the brazing assembly; Step 4: Place the welded assembly from step 3 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3 × 10 –3 Pa, then 5 ~ 30 ℃ min –1 The vacuum brazing furnace is heated to 30-120°C above the melting point of the brazing material at a heating rate, then kept warm for 5-60 min, and finally heated at 1-10°C min –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain a composite material or ceramic and metal brazing joint.

[0015] The present invention has the following significant beneficial effects: (1) Innovatively utilizing the unique advantages of the three-dimensional network structure of porous niobium provides an ideal uniform dispersion environment for element diffusion, accurately controls the growth morphology and size of brittle compounds in the weld from a microscopic level, effectively blocks their continuous chain and flake aggregation trend, and comprehensively strengthens the comprehensive mechanical properties of the brazed joint. Whether it is tensile strength, shear strength or fatigue resistance, it has been significantly improved, greatly enhancing the reliability and durability of the connection under complex working conditions, and providing a solid guarantee for the connection of key components of high-end equipment such as aerospace engines.

[0016] (2) The porous niobium intermediate layer has excellent chemical activity and can rapidly react with key active elements such as Ti and Ni in a variety of commercially available active solders such as Cu-based, Ti-based, and Ni-based solders to form a stable interface bond and exhibit excellent wetting matching performance. It is not restricted by the solder system and can be flexibly matched with solders according to different engineering requirements. It has a wide range of applicability and is highly practical, which greatly facilitates engineering and technical personnel in material selection and process optimization, and accelerates the transformation of technology into practice.

[0017] (3) Taking full advantage of the low thermal expansion coefficient of porous niobium, the overall thermal expansion coefficient of the weld is cleverly adjusted to achieve a near-perfect thermal match with the connected composite materials or ceramics and metal parts, effectively releasing the high residual stress of the joint, and reducing the risk of thermal stress damage from the root, ensuring that the connection structure is dimensionally stable and has reliable performance under thermal cycling conditions, providing a highly innovative and effective solution to the problem of cross-material connection.

[0018] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: Step 2 uses 800-mesh silicon carbide sandpaper to grind the clean composite material or ceramic surface to be welded to remove scratches on the composite material or ceramic surface to be welded, then ultrasonically cleans it in ethanol for 10 minutes, puts it in an oven at 60°C to dry it for use, and the other steps and parameters are the same as those in specific implementation method 1.

[0019] Specific implementation method three: This implementation method is different from specific implementation methods one to two in that: Step 2 uses 600-mesh silicon carbide sandpaper to grind the clean composite material or ceramic surface to be welded to remove scratches on the composite material or ceramic surface to be welded, and then ultrasonically cleans it in ethanol for 15 minutes, puts it in an oven at 80°C to dry it for use, and the other steps and parameters are the same as those of specific implementation methods one to two. Specific implementation method four: This implementation method is different from specific implementation methods one to three in that: the solder described in step three is an active solder such as Cu-based, Ti-based, Ni-based, etc. The other steps and parameters are the same as those of specific implementation methods one to three.

[0020] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: in step 3, the metal matrix is ​​metal niobium, metal copper, metal tungsten, metal molybdenum, CuCr alloy, CuNi alloy, nickel-based high-temperature alloy, titanium alloy, etc. The other steps and parameters are the same as those of specific embodiments 1 to 4.

[0021] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that: Step 4 is 5°C min –1 The vacuum brazing furnace was heated to 30-120℃ above the melting point of the brazing material at a heating rate of 10℃ and then kept warm for 10 min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process. The other steps and parameters are the same as those in specific implementation modes one to five.

[0022] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: Step 4 is carried out at 5°C min –1 The vacuum brazing furnace was heated to 30-120℃ above the melting point of the brazing material at a heating rate of 10℃ and then kept at this temperature for 10 min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process. The other steps and parameters are the same as those in specific embodiments one to six.

[0023] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: Step four is 10°C min –1 The vacuum brazing furnace was heated to 30-120℃ above the melting point of the brazing material at a heating rate of 100℃ and then kept at this temperature for 20 min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process. The other steps and parameters are the same as those in Specific Embodiments 1 to 7.

[0024] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: Step 4 is 10°C min –1 The vacuum brazing furnace was heated to 30-120℃ above the melting point of the brazing material at a heating rate of 100℃ and then kept at this temperature for 15 min. –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process. The other steps and parameters are the same as those in specific embodiments one to eight.

[0025] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 4, the composite material or ceramic is Cf / SiC composite material, C / C composite material or SiN ceramic, etc. The other steps and parameters are the same as those of specific embodiments 1 to 9.

[0026] The following examples are used to verify the beneficial effects of the present invention: Example

[0027] The method for auxiliary brazing of a porous niobium intermediate layer in this embodiment is implemented by the following steps: Step 1: The C / C composite material was cut into blocks of any size by wire cutting, then ultrasonically cleaned in ethanol for 5 min and dried in an oven; Step 2: The clean composite material or ceramic surface to be welded obtained in step 1 is polished with 600, 800, 1000, 1200, 1500, and 2000 mesh silicon carbide sandpaper to remove scratches on the composite material or ceramic surface to be welded, and then ultrasonically cleaned in ethanol for 5 minutes, and placed in an oven at 80°C for drying and then used for standby; Step 3: Grind and polish the surface to be welded of the GH3536 alloy with 800-mesh silicon carbide sandpaper, then ultrasonically clean it in ethanol for 5 min, and put it in an oven at 80 °C to dry it for later use; Step 4: Assemble the porous niobium composite intermediate layer and the BNi2 (6.0–8.0 Cr, 4.0–5.0 Si, 2.75–3.5 B, 2.5–3.5 Fe, bal. Ni, wt%) active brazing filler metal with a thickness of 100 μm according to the formula of brazing filler metal / composite intermediate layer / brzing filler metal, place it between the C / C composite material and the GH3536 alloy to be welded, and complete the brazing assembly.

[0028] Step 5: Place the welded assembly from step 4 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3 × 10 –3 Pa, then at 10 ℃ min –1 The vacuum brazing furnace was heated to 100 °C above the melting point of the brazing material at a heating rate of 3 °C min –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain a composite material or ceramic and metal brazing joint.

Claims

1. A method for auxiliary brazing of porous niobium intermediate layer, characterized in that A method for auxiliary brazing of a porous niobium intermediate layer is carried out according to the following steps: Step 1: Ultrasonic clean the composite material or ceramic to be welded in ethanol for 5 to 15 minutes and dry it in an oven; Step 2: The clean composite material or ceramic surface to be welded obtained in step 1 is polished with 600-2000 mesh silicon carbide sandpaper to remove scratches on the composite material or ceramic surface to be welded, and then ultrasonically cleaned in ethanol for 5-15 minutes, and placed in an oven at 60-80°C for drying and then used for standby; the metal is polished with 400 mesh, 600 mesh and 800 mesh sandpaper in turn, and then ultrasonically pretreated with ethanol for 5-15 minutes, and placed in an oven at 60-80°C for drying and then used for standby; Step 3: Assemble the porous niobium and commercially available active brazing filler metal according to the structure of brazing filler metal / porous niobium / brzing filler metal, place them between the surfaces to be welded of the composite material or ceramic and the metal, complete the brazing assembly, and obtain the welded parts; Step 4: Place the workpieces to be welded in step 3 into a vacuum brazing furnace and evacuate until the vacuum degree is less than 3 × 10 –3 Pa, then 5 ~ 30 ℃ min –1 The vacuum brazing furnace is heated to 30-120℃ above the melting point of the brazing material at a heating rate, then kept warm for 5-60 min, and finally heated at 1-10℃ min –1 The vacuum brazing furnace is cooled to room temperature at a cooling rate to complete the brazing process and obtain a composite material or ceramic and metal brazing joint.

2. A method for auxiliary brazing of a porous niobium intermediate layer as claimed in claim 1, characterized in that In step 1, the composite material or ceramic is cut by wire cutting to obtain a block with a size of 5 mm × 5 mm × 5 mm, and then ultrasonically cleaned in ethanol for 5 to 15 min and dried in an oven for later use.

3. A porous niobium intermediate layer auxiliary brazing method as claimed in claim 1, characterized in that In step one, the composite material or ceramic includes carbon fiber reinforced carbon-based (C / C) composite material, carbon fiber reinforced silicon carbide-based (C / SiC) composite material, silicon carbide fiber reinforced silicon carbide-based (SiC / SiC) composite material, silica fiber reinforced silica-based (SiO2 / SiO2) composite material, boron fiber reinforced aluminum-based (B / Al) composite material, silicon carbide reinforced aluminum-based (SiC / Al) composite material, silicon carbide fiber reinforced copper-based (SiC / Cu) composite material, glass fiber reinforced alumina ceramic-based composite material, etc.

4. A porous niobium intermediate layer auxiliary brazing method as claimed in claim 1, characterized in that In step 1, the ceramic includes Al2O3 ceramic, SiC ceramic, SiN ceramic, graphite, BN ceramic, AlN ceramic or diamond, B4C ceramic, TiB2 ceramic, ZrO2 ceramic, AlN ceramic, etc.

5. A porous niobium intermediate layer auxiliary brazing method as claimed in claim 1, characterized in that In step 2, the metal includes metal niobium, metal copper, metal tungsten, metal molybdenum, CuCr alloy, CuNi alloy, nickel-based high-temperature alloy, titanium alloy, etc.

6. A porous niobium intermediate layer auxiliary brazing method as claimed in claim 1, characterized in that In step 3, the solder includes BNi2 (6.0-8.0 Cr, 4.0-5.0 Si, 2.75-3.5 B, 2.5-3.5 Fe, bal. Ni, wt.%), Ag-27.5Cu-4.5Ti (wt.%), Ti-27.5Si (wt.%), Ti-25Ni-10Nb (wt.%), Cu-12Mn-3.5Ni (wt.%), Ti-66Ni (wt.%), BNi7 (13.0-15.0 Cr, 4.0-5.0 Si, 2.75-3.5 B, 3.0-4.0 Fe, bal. Ni, wt.%), Ag-28Cu (wt.%), Ag85Mn15 (wt.%), Ti-70Cu-Ni (wt.%), Cu-7P (wt.%), Zn-22Al(wt.%).

7. A method for auxiliary brazing of porous niobium intermediate layer according to claim 1, characterized in that In step three, the solder is in the form of foil or solder paste.

8. A method for auxiliary brazing of porous niobium intermediate layer according to claim 1, characterized in that In step 3, the thickness of the porous niobium is 0.2 to 1 mm.

9. A method for auxiliary brazing of porous niobium intermediate layer according to claim 1, characterized in that 1 In step 4, BNi2 (6.0-8.0 Cr, 4.0-5.0 Si, 2.75-3.5 B, 2.5-3.5 Fe, bal. Ni, wt.%) active brazing filler metal is used to braze composite materials or ceramics and metals, and the heating rate is 15 ℃ min –1 The brazing temperature is 1020 ~ 1170 °C, the temperature is kept for 5 ~ 20 min, and the cooling rate is 3 °C min –1 .

Citation Information

Patent Citations

  • Method for improving TC4 and ceramic brazing performance through adding foam copper middle layer

    CN106270889A

  • A method for assisted brazing of porous negative expansion ceramic interlayer

    CN109369209B

  • Method for relieving residual stress of brazed joint

    CN103143805A

  • Braze-welding method for ceramic or ceramic-based composite material and metal through composite interlayer

    CN106493443A

  • Auxiliary brazing method for CuO nano structure enhanced foam copper intermediate layer

    CN107570830A

Cited By

  • Brazing method for aluminum nitride ceramic and oxygen-free copper and composite brazing filler metal

    CN120715330A

  • Brazing method for synchronously achieving welding seam porous structure during porous material welding

    CN121514630A

  • Ti2AlNb-based alloy and Ti65 alloy welding process, brazed joint and application

    CN122703092A